(untitled) (Samarra Journal of Pure and Applied Science, 2026)
The research was carried out in the laboratories and fields of the College of Agriculture - Department of Plant Protection - where six natural and biological agents were tested to control the Rhizctonia rot disease on wheat, Sham 6, caused by the fungus Rhizctonia solani (cloves, rosemary oil, local propolis), serratia protemaculance , gum arabic, food mushroom culture residues), propolis treatment excelled in laboratory inhibition of the fungus, germination rate, reduction of disease rate and severity, leaf area, vegetative and root dry weight, plant height, and root total length were 74.53%, 100%, 0%, 0%, 61.77 cm2 and 8.12 gm, 3.67 gm, 87.52 cm, and 24.05 cm. The propolis sample was analyzed to detect the active substances, so the compound (E)-9-Octadecenoic acid ethyl ester was the highest concentration